Meghretsots St. Astvatsatsin church in Shushi - Yeranyan, Nzhdeh (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The Meghretsos St. Astvatsatsin church is located in the upper district of the city of Shushi. Immigrants from Meghri constructed it in the eponymous quarter in 1838. During the Soviet period, the church was demolished and converted into an open-air summer cinema. According to local informants, since it was impossible to demolish the church’s solid, thick walls, most of the walls were destroyed by explosion. The foundation walls, which were higher than one meter, were incorporated beneath the asphalt. To verify this information and restore the church’s integrity, rescue excavations were conducted on site in 2017. The excavations validated a structure measuring 24.75 by 12.77 meters with walls up to 1.3 meters thick. Through its spatial and architectural solutions, the Meghretsotz church replicates the typology of churches known in Shushi and other regions of Artsakh during the 17th–19th centuries.